Elevated white blood cell counts in ischemic stroke patients are associated with increased mortality and new vascular events - Vo, Thao Phuong; Kristiansen, Marie Hvelplund; Hasselbalch, Hans Carl; Wienecke, Troels (Frontiers in Neurology, 2023)
Background and purpose High levels of white blood cells (WBC) in ischemic stroke have been shown to increase the risk of new vascular events and mortality in short and intermediate follow-up studies, but long-term effects remain unknown. We studied whether elevated levels of WBC in ischemic stroke patients are associated with new vascular events and mortality in a 10-year follow-up period. Methods We included ischemic stroke patients hospitalized between 2011 and 2012, categorizing their WBC counts within 48 h of stroke onset as high or normal (3.5–8.8 × 109 mmol/L; >8.8 × 109 mmol/L). Using Aahlen Johansen and Cox proportional hazard models with competing risk, we analyzed the association between WBC levels and new vascular events. Kaplan–Meier and standard Cox proportional hazard models were used to assess the risk of all-cause mortality. Results Among 395 patients (median age 69, [IQR: 63, 78], female patients 38,0%), 38.5% had elevated WBC at admission. During the 10-year follow-up, 113 vascular events occurred, with 46% in patients with elevated WBC and 54% in patients with normal WBC. After adjusting for relevant factors, elevated WBC levels were independently associated with increased risk of new vascular events (HR: 1.61, CI: 1.09–2.39 p < 0.05) and death (HR: 1.55, CI: 1.15–2.09, p < 0.05). Conclusion Elevated WBC levels in ischemic stroke patients are linked to a higher risk of new vascular events and mortality. Thus, ischemic stroke patients with elevated WBC without clinical infection need special attention to investigate possible underlying conditions to prevent future vascular events and reduce mortality. The interpretation of our results is limited by the absence of adjustment to premorbid functional status, stroke severity, and stroke treatment.